The IMPORTANCE OF DETERMINING THE STATUS OF THE FREE PAPUA ORGANIZATION TO AVOID THE POTENTIAL FOR FUTURE WAR IN INDONESIA - Ardhes Leuanan (Jurnal Suara Keadilan, 2026)
The armed conflict and rebellion that occurred between the Free Papua Operation (OPM) group and the Indonesian State had become the concern of the international community. This armed conflict began in 1963, where the Papuan people felt they had to separate themselves by wanting a referendum from Indonesia, which eventually initiated an armed conflict. This paper aims to analyze the characteristics of this armed conflict based on the perspective of International Humanitarian Law. It primarily examines the qualifications of armed conflict under the 1949 Geneva Conventions and International Humanitarian Law. This paper concludes that the status of the OPM in this conflict can be qualified as an unlawful combatant. This armed conflict has different party characteristics, namely between the legitimate Government of a State and an organized movement based in another State. Thus, this type of armed conflict between the OPM group and the Indonesian Government is included in the gray zone conflict which will affect the concept of a military approach in order to maintain the integrity and ideology of the nation.